CP-065 Switching antiretroviral therapy: reasons and associated costs in a cohort of Hiv-Infected patients. (24th March 2015) - Florit, M; Retamero, A; Luque, S; Grau, S; Garcia, R; Guelar, A; Knobel, H; Salas, E
Abstract : Background: Several factors, such as toxicity, virological failure or low adherence can justify the need for switching antiretroviral therapy (ART) in HIV patients. Purpose: To study the reasons for switching ART in an HIV unit in a tertiary hospital. Secondary objectives were to study the number of switches over time and their estimated annual cost (EAC). Material and methods: We recorded ART switches performed every 6 months from January 2012–June 2014 in our cohort of 1, 550 HIV-infected patients. Date collected: previous and new ART, reason for switching and EAC (difference in the daily acquisition cost between the new and the previous ART calculated for 365 days of treatment). The Spearman test was used for bivariate correlations. Results: 685 switches were performed: 117 (7.5%), 98 (6.3%), 130 (8.4%), 157 (10.1%) and 183 (11.8%) in each 6-month period. An increase in the number of changes/6 months over time was observed (Spearman rho: 0.9; p < 0.05). The total number of switches/6 months correlated only with toxicity (Spearman rho: 0.95; p < 0.05). Conclusion: An increase in the number of switches per 6-month period was observed over time. Total number of switches/6 months was correlated to those associated with toxicity. The availability of new and less toxic ARTs may explain these results. Toxicity remained the most frequent reason for switching, representing between 58% and 63% depending on the year. Switches due to virological failure entailed an increase in the EAC, while those due to simplification brought cost savings. Overall, the economic impact of this strategy on the annual acquisition cost of ARTs in our hospital seems to be minimal. References and/or Acknowledgements: No conflict of interest.